Introducing Winnicott: Jacobs, M (1995) Winnicott. London: Sage 163 pages ISBN 0-8039-8596-7 - Kelly, Kevin J (PINS-Psychology in Society, 2026)
This little book on Winnicott, by Michael Jacobs, is part of the Sage series - "Key figures in counselling and psychotherapy". It follows the same structure as other titles in the series and begins with a biographical sketch. This is followed by a review of Winnicott’s major contributions to theory and practice, a chapter on criticisms and rebuttals of his work, and an evaluation of his influence The book ends with a select bibliography of Winnicott’s works.